Productivity and Wage Effects of Firm-Level Collective Agreements: Evidence from Belgian Linked Panel Data - Andrea Garnero; Francois Rycx; Isabelle Terraz (Institute of Labor Economics (IZA), 2018)
How do firm-level collective agreements affect firm performance in a multi-level bargaining system? Using detailed Belgian linked employer-employee panel data, our findings show that firm agreements increase both wage costs and productivity (with respect to sector-level agreements). Relying on a recent approach developed by Bartolucci (2014), they also indicate that firm agreements exert a stronger impact on wages than on productivity, so that profitability is hampered. However, this rent-sharing effect only holds in manufacturing. In private sector services, the raw wage premium associated to firm agreements is entirely driven by compositional effects. Furthermore, estimates show that firm agreements lead to significantly more rent-sharing among firms operating in less competitive environments. Firm agreements are thus mainly found to raise wages beyond productivity when the rents to be shared between workers and firms are relatively big. Overall, this suggests that firm-level agreements benefit to both employers and employees – through higher productivity and wages – without being very detrimental to firms' performance.
Keywords: C33; J24; J31; 330; collective bargaining; productivity; labour costs; linked panel data